Dairy of a wimpy kid Wrecking ball - Kinney, Jeff (London: Penguin, 2021)
THE ONE WITH THE HOME IMPROVEMENTS The fourteenth laugh-out-loud, fully-illustrated Diary of a Wimpy Kid book from #1 international bestselling author Jeff Kinney! A global phenomenon with 250 million copies of the series sold worldwide! Big changes are in store for Greg Heffley and his family. They are making home improvements! But with unwelcome critters, toxic mould and the walls coming down, soon Greg discovers renovations aren't all they are cracked up to be. When the dust finally settles, will the Heffleys be able to stay.
WHAT'S IN DIARY OF A WIMPY KID? 50% words, 50% cartoons, 100% hilarious! Stories that all readers can't wait to get their hands on Laughter guaranteed!